Case report: Novel TBX5-related pathogenic mechanism of Holt–Oram syndrome - Lang, Yuheng; Zheng, Yue; Qi, Bingcai; Zheng, Weifeng; Zhao, Chengxiu; Zhai, Hu; Wang, Gang; Luo, Zhiqiang; Li, Tong (Frontiers in Genetics, 2023)
Holt-Oram syndrome is a rare genetic disorder characterised by upper limb abnormalities, congenital heart defects and/or conduction abnormalities. Sequence alteration of the TBX5 gene is correlated to HOS. We present the case of a 24-year-old female with known upper limb alteration (congenital dysplasia in wrist and elbow joint) and anomalous left main trunk arising from the right coronary sinus. The patient obtains genetic inheritance of the base T (reference C) atrs883079 from her mother and the base C (reference T) at rs10850326 from her father, which both belong to the 3’-untranslated region (UTR) of the TBX5 gene. However, there was no mutation and SNP at other exon areas. To further explore the TBX5 effects on cardiomyocytes, the HL-1 cell line and TBX5 knockdown were utilized. qPCR analysis demonstrated that TEKT2, TEKT4 and SPTB expressions decreased after TBX5 knockdown and ChIP analysis further revealed that TBX5 binds TEKT2, TEKT4 and SPTB promoter regions to promote the transcription of the genes. Therefore, a novel TBX5 pathogenic mechanism of an individual with Holt-Oram Syndrome may be discovered and more researches are still required to validate these findings.